Influence of BrineâRock Parameters on Rock Physical Changes During CO2 Sequestration in Saline Aquifer - Md Yusof, M.A. (Springer Science and Business Media Deutschland GmbH, 2021)
Injection of carbon dioxide (CO2) into saline aquifer for sequestration is a promising approach to mitigate the climate issue. However, reactive interactions between various CO2âbrineârock parameters have significantly affected the CO2 sequestration. Factors such as brine type, brine salinity, reactive pore surface area and contact time were found to significantly alter the physical rock properties. Until now, a systematic study on the dominance and degree of influence of each factor has yet to be carried out. To further understand environmental factors that impact dissolution and precipitation mechanisms, we combined the four influencing factors in static batch experiments and observed the physical changes on formation rock and ranked them according to the level of dominance by using Taguchi method. Static batch CO2âbrineârock experiments were carried out by injecting supercritical CO2 in an aging cell filled with brines and cubes of rock samples. The results showed that brine salinity is the most notable factor, followed by reactive pore surface area and duration of exposure. Comparison of field emission scanning electron microscope images taken before and after experiments indicated changes among potassium chloride (KCl), sodium chloride (NaCl) and calcium chloride (CaCl2) brines resulting in dramatic changes of pore spaces because of mineral dissolution, deposited salts, and fines migration. Â© 2021, King Fahd University of Petroleum & Minerals.